1999
DOI: 10.1046/j.1365-2036.1999.00465.x
|View full text |Cite
|
Sign up to set email alerts
|

Ranitidine bismuth citrate, tetracycline, clarithromycin twice‐a‐day triple therapy for clarithromycin susceptible Helicobacter pylori infection

Abstract: Twice-a-day ranitidine bismuth citrate, tetracycline, clarithromycin triple therapy was well tolerated and effective for the treatment of H. pylori infection in patients with clarithromycin-susceptible H. pylori.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
4
0

Year Published

2000
2000
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 20 publications
1
4
0
Order By: Relevance
“…Combinations that contained clarithromycin had the highest eradication rates. Clarithromycin containing regimens that have twice a day dosing may have better compliance, are cheaper and yet have good cure rates [22]. Similar eradication rates were seen when pantoprazole was used instead of omeprazole [23] and overall, there seems to be no PPI with an advantage over another such that the PPIs can be used interchangeably.…”
Section: Commonly Used Triple Therapies and The Effect Of Acid Suppresupporting
confidence: 66%
“…Combinations that contained clarithromycin had the highest eradication rates. Clarithromycin containing regimens that have twice a day dosing may have better compliance, are cheaper and yet have good cure rates [22]. Similar eradication rates were seen when pantoprazole was used instead of omeprazole [23] and overall, there seems to be no PPI with an advantage over another such that the PPIs can be used interchangeably.…”
Section: Commonly Used Triple Therapies and The Effect Of Acid Suppresupporting
confidence: 66%
“…Studies reporting duplicate data were excluded. After careful evaluation of the full texts, 48 studies reported detailed regimen and their eradication rates according to antibiotic resistances were finally included 4,5,12–57 …”
Section: Resultsmentioning
confidence: 99%
“…Reasons for the conflicting results between the different studies are unknown. Treatment with RBC, tetracycline and clarithromycin for one to two weeks has been reported by two authors, with ITT eradication rates of over 90% in more than 100 patients (52,53).…”
Section: Rbc Triple Therapy In Ppi Triple Therapy Failuresmentioning
confidence: 92%